Synthesis of Reduced Graphene Oxide-Bentonite Composite and Its Application as a Lead(II) Ion Adsorbent - Bartholomeus Lavelim; Lia Destiarti; Adhitiyawarman Adhitiyawarman; Risya Sasri (Universitas Gadjah Mada, 2023)
The use of reduced graphene oxide (rGO) as an adsorbent has challenges to overcome. Although rGO has a large surface area, its solubility in water is very low. In this study, bentonite is added to reduce the use of rGO mass and increase the dispersibility of the adsorbent. The rGO-bentonite (rGOB) was characterized by XRD, FTIR, SEM-EDX, and XRF. The adsorption activity was tested in a Pb ion solution, derived from AAS. The XRD pattern of GO, rGO, and rGOB of 2q were observed at 10.90°, 24.88°, and 26.66°, respectively. The FTIR spectrum showed that GO has C=C, C-O, C=O, and O-H, while in rGO, C=O disappears, and there was a significant decrease in the O-H and C-O peaks. The rGOB has identical spectra with rGO and yet has an additional peak from bentonite O-Si-O. The GO and rGO form agglomerate while rGOB looks more dispersed. The C/O ratio increases from GO to rGO because of the reduction process. The bentonite is Ca-bentonite with main components Al2O3, SiO2, and CaO. The results showed that the rGOB composite could reduce the use of rGO by up to 80% and have an adsorption performance similar to rGO with an adsorption capacity of 217 mg/g.